Surface treatment systems for concrete in marine environment: Effect of concrete cover thickness - Medeiros,Marcelo Henrique Farias de (2016)
Abstract There are some ways to extend the service life of a reinforced concrete structure. This paper focuses on the extension of the service life by treating the surface of reinforced concrete, specifically on the effect of the concrete cover thickness on the surface treatment system efficacy. Thus, chloride migration tests were performed and diffusion chloride coefficients were calculated. The service life of each case (treated or non-treated concrete) was estimated using these data and Fick's second law of diffusion. Results indicated that the thicker the concrete cover is, the greater the efficacy of the concrete surface treatment system will be. The dissemination of this information is important, since it is almost intuitive to think that the effect of a surface treatment system depends only on itself and this study shows the opposite.